Implementation of the Class 5 Teaching Campus Program at Junior High School 4 Sibolga - Tiurmaida Margaretta Sanggam Sirait; Hery Pudjoprastyono (LPPM Sekolah Tinggi Teknologi Nusantara Lampung, 2023)
The teaching campus is one of the Merdeka Learning Kampus Merdeka programs, often referred to as MBKM. The teaching campus was formed when Indonesia was hit by COVID-19, which had an impact on the education sector and resulted in the education system being laid off so that many students did not focus on their studies, which resulted in a lack of understanding of literacy and numeracy. Thus, the teaching campus has a very important goal, namely the development of learning models, and also fosters creativity and innovation in learning so as to increase the understanding of literacy and numeracy. School. The school's target for this teaching campus program is Junior High School 4 Sibolga. This study aims to determine how to implement it and its impact on target schools in the areas of understanding literacy, numeracy, technology adaptation, and the school administration department. The research technique used was descriptive-qualitative, collecting data through interviews, observation, or documentation. The results showed that the teaching campus program had a practical impact on increasing student literacy and was quite effective in increasing student numeracy at Junior High School 4 Sibolga.